2006
DOI: 10.1529/biophysj.105.075366
|View full text |Cite
|
Sign up to set email alerts
|

Sonoporation from Jetting Cavitation Bubbles

Abstract: The fluid dynamic interaction of cavitation bubbles with adherent cells on a substrate is experimentally investigated. We find that the nonspherical collapse of bubbles near to the boundary is responsible for cell detachment. High-speed photography reveals that a wall bounded flow leads to the detachment of cells. Cells at the edge of the circular area of detachment are found to be permanently porated, whereas cells at some distance from the detachment area undergo viable cell membrane poration (sonoporation).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
306
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 447 publications
(334 citation statements)
references
References 41 publications
16
306
1
1
Order By: Relevance
“…Consequently, different microbubble-cell interactions may induce different routes of drug internalization. With high-speed bright-field microscopy, the effects of microbubbles on cells have been studied before [36][37][38]. However, this technique does not provide information on drug uptake.…”
Section: Link Between Microbubble-cell Interactions and Uptake Mechanismmentioning
confidence: 99%
“…Consequently, different microbubble-cell interactions may induce different routes of drug internalization. With high-speed bright-field microscopy, the effects of microbubbles on cells have been studied before [36][37][38]. However, this technique does not provide information on drug uptake.…”
Section: Link Between Microbubble-cell Interactions and Uptake Mechanismmentioning
confidence: 99%
“…It has been found that sonoporation is enhanced significantly when cavitation bubbles are present during the acoustic exposure, suggesting that a fluid dynamic interaction between cavitation bubbles and cells is responsible for membrane poration [17,31,32], The physical mechanism of sonoporation is not well understood and thus the dependence of membrane permeabilization on the cavitation parameters is not yet known [33,34], A better understanding of the physical mechanisms responsible for the poration of the cell membrane is crucial for the optimization of this technique. As a result many groups are examining ultrasound-generated cavitation bubble dynamics and the resulting fluid velocities to determine the shear stresses and exposure times required to achieve sonoporation, cell detachment, and cell lysis [16,17,29,35,36]. …”
Section: Implications For Molecular Delivery and Acoustic Cavitation mentioning
confidence: 99%
“…As a result, there is an increasing interest to use pulsed laser microbeams for precise cellular manipulation, including laserinduced cell lysis [1], cell microdissection and catapulting [2][3][4][5], cell collection, expansion, and purification [6][7][8], cellular microsurgery [9][10][11], and cell membrane permeabilization for the delivery of membrane-impermeant molecules into cells [12 15], The processes of laser-induced optoinjection and optoporation offer the ability to load cells with a variety of biomolecules on short time scales (milliseconds to seconds) through optically produced cell membrane permeabilization [12,14,15], Despite the innovative utilization of laser microbeams in cell biology and biotechnology, only recently have studies provided insight regarding the mechanisms that mediate the interactions of highly focused pulsed laser beams with cells [16][17][18][19][20][21][22], A better understanding of these processes will prove critical to the continued development of laser microbeams for both research and practical applications. In previous studies, we provided a detailed characterization of the physics involved in the interaction of highly-focused nanosecond laser microbeams with cells [19,20], However, it is important to relate these physical effects to the biological response of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, directed fluid transport over short distances or micro-manipulation of adjacent objects are attractive perspectives. While solid, free, elastic or composite interfaces and bubble manipulation with acoustic or shock waves might be considered as a means of control of individual jetting bubbles (Chahine 1977;Blake & Gibson 1981;Gibson & Blake 1982;Blake et al 1986;Blake, Taib & Doherty 1987;Shima et al 1989;Brujan et al 2001a,b;Robinson et al 2001;Tomita et al 2002;Wolfrum et al 2002Wolfrum et al , 2003Ohl et al 2006;Wang & Blake 2010, their use can be problematic owing to the introduction of additional constraints and the need for proper placement. Generation of a single asymmetric bubble (Lim et al 2010) or of a bubble pair (Lauterborn 1974;Lauterborn & Vogel 1984;Lauterborn & Hentschel 1985;Testud-Giovanneschi, Alloncle & Dufresne 1990;Tomita, Shima & Sato 1990;Blake et al 1993;Jungnickel & Vogel 1994;Tomita, Sato & Shima 1994;Fong et al 2009;Sankin, Yuan & Zhong 2010) with predetermined jetting behaviour by means of optical breakdown in the bulk of transparent liquids appear as a less invasive and more versatile tool for control and optimization of jet properties.…”
mentioning
confidence: 99%